High spatio-temporal resolution dynamic water monitoring using multi-source Chinese Gaofen imagery: a case study in the Eastern Nile Basin - Nie, Xiaoyan; Xu, Jia; Ge, Ying; Zhou, Wenyi (Frontiers in Earth Science, 2025)
The East Nile Basin (ENB) is a major water source for several African countries, and the supply, distribution, and management of water resources in the basin are directly related to the survival and development of millions of people. However, most of the basin falls within arid or semi-arid regions, and the uneven distribution of water resources severely limits the development of the countries within the basin. Achieving accurate monitoring and effective management of water resources has become a critical issue for sustainable development in this region. A robust adaptive threshold method considering boundary optimization was proposed to accurately extract water body information from GF-1and GF-6 WFV imagery. The study analyzed the spatio-temporal dynamic changes of six key lakes in basin countries, including Egypt, Ethiopia, and Sudan from 2019 to 2024. The findings were as follows: (1) The proposed water extraction method effectively addressed the issue of uneven spectral index gradients, with an overall accuracy of over 97.67% and a Kappa value exceeding 95.24%. It was able to accurately and efficiently extract lakes in arid regions. (2) High spatiotemporal resolution monitoring revealed the variation patterns of the lakes. The interannual changes of Tana, Roseires, Merowe, and Nasser were not significant, with notable seasonal variations, the low-water-level period occurring in July and the high-water-level period in September or October. For GERD and Toshka, the interannual variation was large, with each increase occurring between July and October. (3) The variation in lake areas was primarily attributed to precipitation in the upstream Blue Nile, artificial water storage by dams, and other factors. Tana was mainly affected by precipitation, while GERD’s changes were primarily related to precipitation and its own water storage, Roseires, Merowe, and Nasser, as artificial reservoirs, were influenced by their own water storage and the storage in upstream reservoirs, while Toshka’s changes were related to overflow from Nasser’s high water levels. The current research findings could provide scientific guidance for water resources assessment and management in the ENB.